A Scanner and Parser for Z Specifications - Maria Ulfah Siregar; John Derrick (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2018)
Coding either a scanner or a parser from beginning has many disadvantages such as tedious, could raise many errors, needs much times and effort, etc. All of these could result less scanner or parser. This paper describes our research on implementing a scanner and parsers for Z specifications. Rather to code them from scratch, we use tools that have specialities on creating such tasks. These tools generate several Java files which can be integrated with a main program in Java. Our research produces a scanner and parser for Z specifications. These tools may benefit Z specifications to be studied further.